The global football league : transnational networks, social movements and sport in the new media age - Millward, Peter (Global culture and sport, 2011)
This book critically addresses the themes that have come to define the global flow of images, capital and people that exist in contemporary football today. In doing so, this text tackles issues of globalization in the English Premier League and unpicks what this means to fan groups in the UK, U.S.A, Scandinavia and East Asia. The text also explores issues connected to the growing trend of overseas ownership in the English Premier League and by doing so, the book draws upon a range of sociological theories to tell the story of the local and global repertoires of action emanating from the popular protests at Liverpool and Manchester United football clubs.
Keywords: Social networks; Social movements; International business enterprises; Globalization; jalkapallo; urheilu; sosiaaliset verkostot; yhteiskunnalliset liikkeet; kansainväliset yritykset; globalisaatio